Economic and Technical Efficiency Aspects of Biogas Production for Farm Waste Processing: Case of Slovakia Agriculture - Bielik, Peter; Adamickova, Izabela; Sandor, Erik; Belinska, Stefaniia; Belinska, Janina (Research on World Agricultural Economy, 2026)
The article focuses on evaluating both the economic and technical efficiency of biogas plants that are designed to process agricultural waste and farm by-products. The primary aim is to provide a comprehensive assessment of economic performance, applied technological solutions, and different capacity configurations, while also examining their influence on biogas production efficiency and investment payback periods. The study compares various fermentation technologies, analyses the characteristics of input substrates, and explores optimization strategies aimed at maximizing energy output. Economic and technical efficiency is understood as the ability of a biogas plant to utilize available resources in the most effective way to produce energy and other outputs. To improve the allocation of agricultural land used for biomass production, the research applies the methodology of technical efficiency frontiers. This approach helps identify optimal production combinations. Furthermore, correlation and regression analysis are used to measure the relationship between farm income and selected variables, allowing the identification of the most influential factors affecting financial performance.Sensitivity analysis is also conducted to examine how key economic indicators, such as yields, Net Present Value (NPV), and Internal Rate of Return (IRR), respond to changes in input parameters. The results emphasize the crucial determinants of profitability and highlight the role of biogas plants in supporting sustainable agricultural development. ER